The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3803/enm.2014.29.2.163
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Phosphorylates Tyrosine Residue 464 of Tub and Translocates Tubby into the Nucleus in HIRcB Cells

Abstract: BackgroundThe tubby protein has a motif that might be relevant for its action in the insulin signaling pathway. Previous studies have indicated that tubby undergoes phosphorylation on tyrosine residues in response to several stimuli and is known to localize in the nucleus as well as in the plasma membrane. However, the relationship between phosphorylation and nuclear translocation is not well understood. Here, we report that insulin directly phosphorylates tubby, which translocates into the nucleus.MethodsThe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Loss-of-function mutations in daf-10 also suppressed the expanded fan phenotype of odr-1 mutants (Figure 4—figure supplement 1). The subcellular localization of Tubby proteins can be altered by cellular signaling (Chen et al, 2012; Kim et al, 2014; Santagata et al, 2001); we asked whether the expanded fan-like structure in odr-1 mutants is accompanied by increased ciliary TUB-1 levels. Indeed, we found that odr-1 mutants showed enrichment of a TUB-1 fusion protein in AWB cilia as compared to levels at the PCMC (Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
“…Loss-of-function mutations in daf-10 also suppressed the expanded fan phenotype of odr-1 mutants (Figure 4—figure supplement 1). The subcellular localization of Tubby proteins can be altered by cellular signaling (Chen et al, 2012; Kim et al, 2014; Santagata et al, 2001); we asked whether the expanded fan-like structure in odr-1 mutants is accompanied by increased ciliary TUB-1 levels. Indeed, we found that odr-1 mutants showed enrichment of a TUB-1 fusion protein in AWB cilia as compared to levels at the PCMC (Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
“…As such, we anticipate that BdTLP3 Y323F, BdTLP8 V96G and C99G, and BdTLP13 V185G and Q352R will have a strong effect on the protein structure and possibly function. In BdTLP13, Q352 coincided with the Y464 in the Tubby protein and N366 in AtTLP3 [11], a residue that is important for the nuclear translocation of the Tubby protein that is mediated via the insulin phosphorylation of Y464 [65]. Site-directed mutants will inform the role of the identified variant amino acids in BdTLPs under salinity and drought stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, membranes were blocked with 5% bovine serum albumin (BSA) in TBST (50 mM Tris-HCl, pH 7.5 and 150 mM NaCl containing 0.05% Tween 20). 19 The blots were probed overnight with Foxo3 (1:1000, Sigma F-2178), AKT (1:1000, Cell Signaling 4691), pAKT (1:1000, Cell Signaling 4060), and phospho-Foxo3 (1:1000, Cell Signaling 2599) in 5% BSA containing TBST (10 mM Tris pH 8.0, 150 mM NaCl, 0.05% Tween-20). After incubating with an anti-rabbit secondary antibody coupled with horseradish peroxidase, the immunocomplexes were visualized with enhanced chemiluminescence.…”
Section: Methodsmentioning
confidence: 99%